Species invasions and the phylogenetic signal in geographical range size. Issue 9 (30th October 2018) - Pigot, Alex L.; Dyer, Ellie E.; Redding, David W.; Cassey, Phillip; Thomas, Gavin H.; Blackburn, Tim M.
Abstract: Aim: Accelerating rates of anthropogenic introductions are leading to a dramatic restructuring of species distributions globally. However, the extent to which invasions alter the imprint of evolutionary history in species geographical ranges remains unclear. Here, we provide a global assessment of how the introduction, establishment and spread of alien species alters the phylogenetic signal in geographical range size using birds as a model system. Location: Global. Time period: Contemporaneous. Taxa: Birds. Methods: We compare the phylogenetic signal in alien range size with that of native distributions of species globally ( n =  9, 993) and across different stages in the invasion pathway, from introduced ( n =  965) to established species ( n =  359). Using stochastic simulations, we test whether differences in phylogenetic signal arise from nonrandom patterns of species introduction, establishment or spread. Results: Geographical range size in birds exhibits an intermediate phylogenetic signal, driven by the spatial clustering of closely related species. Nonrandom introductions, biased towards wide‐ranging species from particular clades and regions, produce an anomalously strong phylogenetic signal in the native range size of introduced species. In contrast, the phylogenetic signal in alien range size is substantially weaker than for native distributions. This weak phylogenetic signal cannot be explained by a lack of time for dispersal but is instead regulated by phylogenetic correlations across species in the location and number of introduction events. Main conclusions: We demonstrate that the effects of anthropogenic introductions on the phylogenetic signal in range size vary across different stages in the invasion pathway. The process of transport and introduction amplifies the phylogenetic signal in the pool of potential invaders, whereas the subsequent pattern of spread decouples variation in alien range size from phylogenetic ancestry. Together, our findings suggest that evolutionary relatedness is likely to be a relatively weak predictor of the spread of invasive species.